A distributed compensating strategy for power systems pre-protection against disruptive contingencies using heterogeneous FACTS devices - Wang, Zhaoxu; Zhai, Chao (Electric power systems research, 2022)
The responsive and effective pre-protective actions are vital to the resilience of electrical power systems. This paper addresses the online pre-protection problem of power systems subject to disruptive disturbances caused by contingencies. A novel distributed optimization algorithm for flexible alternate current transmission systems (FACTS) devices is proposed to adjust the branch impedance and voltage phase angle with the aid of thyristor-controlled series compensation (TCSC) and thyristor-controlled phase shifting transformer (TCPST), which enables to regulate power flow and eliminate the disruptions caused by bus overloads and transmission line faults. Moreover, theoretical analysis is conducted to guarantee the convergence of numerical algorithm for solving the distributed optimization problem. Finally, numerical simulations are carried out to validate the proposed optimization algorithm on IEEE 9 bus system, and a performance index is proposed to better compare control effects with existing centralized control algorithm. •Create a novel network model for power grids to decouple the physical layer and cyber layer.•Develop a distributed optimization algorithm by integrating FACTS devices for the real-time protection of power systems.•Provide rigorous theoretical analysis for the distributed optimization algorithm with guaranteed convergence.